Sam Houston, the tallest Texan - Johnson, William Weber, 1909-.; Reusswig, William (New York : Random House, 1953)
A biography of a leader in Texas' fight for independence who became a governor of the new state and a United States Senator.
Keywords: Houston, Sam, 1793 -- 1863 -- Juvenile literature